Key areas and pathways for carbon emissions reduction in Beijing for the “Dual Carbon” targets - Huang, Ren; Zhang, Sufang; Wang, Peng (Energy policy, 2022)
China pledges to have its carbon emissions peak before 2030 and achieve carbon neutrality before 2060 (“Dual Carbon” targets). Beijing, the capital of China, needs to take the lead in promoting carbon emissions reduction so as to provide an example for other cities. Based on the extended STIRPAT model and LEAP-Beijing model, this paper assesses the key areas and pathways for carbon emissions reduction in Beijing for the period of 2015–2060 under six different policy scenarios. The results show that energy structure upgrading and energy efficiency improvement are the key drivers for the city's emissions reduction. The realization of “Dual-Carbon” targets requires a low-carbon transition of all sectors, and the priority should first be put on the power, transportation and commercial sectors, followed by the thermal and industrial sectors, finally the residential and agricultural sectors. Considering that there exists a large number of carbon leakage, Beijing should start with the PES scenario, strive to achieve carbon peak by 2025, then accelerate the transition to the CES scenario between 2030 and 2035 depending on the ratio of renewable sources in its imported power, and finally achieve carbon neutrality via emissions absorption approaches such as CCUS and carbon sinks by 2060. •There are a lot of carbon leakage from imported heating and power in Beijing.•Power, transportation and commercial sectors are the key areas of emissions reduction in Beijing.•Energy structure upgrading and energy efficiency improvement are Beijing's key drivers of emissions reduction.•Carbon neutrality pathway varies according to the proportion of renewables in Beijing's imported power.